No Effects of Cognitive Remediation on Cerebral White Matter in Individuals at Ultra-High Risk for Psychosis—A Randomized Clinical Trial - Kristensen, Tina D.; Ebdrup, Bjørn H.; Hjorthøj, Carsten; Mandl, René C. W.; Raghava, Jayachandra M.; Jepsen, Jens Richardt M.; Fagerlund, Birgitte; Glenthøj, Louise B.; Wenneberg, Christina; Krakauer, Kristine; Pantelis, Christos; Glenthøj, Birte Y.; et al. (Frontiers in Psychiatry, 2020)
Background Individuals at ultra-high risk for psychosis (UHR) present with subtle alterations in cerebral white matter (WM), which appear to be associated with clinical and functional outcome. The effect of cognitive remediation on WM-organization in UHR-individuals has not been investigated previously. Methods In a randomized, clinical trial, UHR-individuals aged 18-40 years were assigned to treatment as usual (TAU) or TAU plus cognitive remediation for 20 weeks. Cognitive remediation comprised 20 x 2 hours sessions of neurocognitive and social-cognitive training. Primary outcome was whole brain fractional anisotropy derived from diffusion weighted imaging, statistically tested as an interaction between timepoint and treatment group. Secondary outcomes were restricted to five predefined region of interest (ROI) analyses on fractional anisotropy, axial diffusivity, radial diffusivity and mean diffusivity. For significant timepoint and treatment group interactions within these five ROIs, we explored associations between longitudinal changes in WM and cognitive functions / clinical symptoms. Finally, we explored dose-response effect of cognitive remediation on WM. Results A total of 111 UHR-individuals were included. Attrition-rate was 26%. The cognitive remediation group completed in average 12 hours of neurocognitive training, which was considerably lower than per protocol. We found no effect of cognitive remediation on whole-brain FA when compared to treatment as usual. Secondary ROI analyses revealed a nominal significant interaction between timepoint*treatment of AD in left medial lemniscus (P=0.016) which did not survive control for multiple comparisons. The exploratory test showed that this change in AD correlated to improvements of mental flexibility in the cognitive remediation group (p=0.001). We found no dose-response effect of neurocognitive training on WM. Conclusions Cognitive remediation comprising 12 hours of neurocognitive training in average did not improve global or regional WM-organization in UHR-individuals. Further investigations of duration and intensity of cognitive training as necessary prerequisites of neuroplasticity-based changes are warranted.